Defective stratum corneum and early neonatal death in mice lacking the gene for transglutaminase 1 (keratinocyte transglutaminase) - Matsuki, Masato (The National Academy of Sciences, 1998)
The stratum corneum of the skin serves as an effective barrier for maintenance of the internal milieu against the external environment. At the cell periphery of the stratum corneum is the cell envelope, a highly insoluble membranous structure composed of precursor proteins cross-linked by ɛ-(γ-glutamyl)lysine bonds. Transglutaminase 1 (TGase 1; keratinocyte TGase), a membrane-bound isozyme of the TGase family, has been proposed to catalyze this process of assembly. Deficient cross-linking of the cell envelope in some patients with the autosomal recessive skin disorder lamellar ichthyosis (LI) and several mutations of the TGase 1 gene that have been identified in families with LI suggest the importance of this gene in production of the cell envelope. In this study, we generated mice lacking the TGase 1 gene, and we report that they have erythrodermic skin with abnormal keratinization. In their stratum corneum, degradation of nuclei and keratohyalin F-granules was incomplete and cell envelope assembly was defective. The skin barrier function of TGase 1-null mice was markedly impaired, and these mice died within 4–5 h after birth. These results clearly demonstrate that the TGase 1 gene is essential to the development and maturation of the stratum corneum and to adaptation to the environment after birth. Thus, these TGase 1 knockout mice may be a useful model for severe cases of LI.